Inhibition of TNF-alpha reduces transplant arteriosclerosis in a murine aortic transplant model. - Wollin, Martina; Abele, Silke; Bruns, Heiko; Weyand, Michael; Kalden, Joachim; Ensminger, Stephan M.; Spriewald, Bernd M. (Transplant International, 2009)
Experimental and clinical data provide evidence that TNF-alpha contributes to acute and chronic allograft rejection. In this study, we explored the effect of TNF-alpha blockade using the chimeric monoclonal antibody infliximab on the development of transplant arterisoclerosis in a fully mismatched aortic allograft model. Post-transplant treatment of CBA (H2(k)) recipients with 250 mug infliximab (cumulative dose 1.25 mg) reduced luminal occlusion of C57Bl/6 (H2(b)) aortic grafts on day 30 from 77 +/- 5% in untreated controls to 52 +/- 6%. Increasing the dose of anti-TNF-alpha antibody had no further beneficial effect. Treatment with human control immunoglobulin had no effect on intima proliferation. Under TNF-alpha blockade, ICAM-1 and PDGF mRNA expression within the grafts was strongly reduced, whereas iNOS expression was enhanced. The data show that TNF-alpha blockade using infliximab can reduce the development of transplant arteriosclerosis in fully mismatched murine aortic grafts.